Newborn hearing screening: Guide to early diagnosis - Marin-Marín, Diego Franco (2023)
Congenital sensorineural hearing loss is one of the most frequent pathologies of the newborn. To carry out the diagnosis and early detection of this pathology in the pediatric population, specialized audiological tests are required, such as otoacoustic emissions and auditory evoked potentials. Therefore, it is important to have a guide to identify and detect those patients with suspected congenital sensorineural hearing loss.